Tutela do patrimônio ambiental espeleológico no direito material brasileiro - Souza, Adriano Andrade de (2012)
Brazilian speleological patrimony is formed by a set of material and immaterial goods of invaluable natural and cultural values, and it`s preservation is essential to guarantee to present and future generations a healthy environment. Until recently, this environmental patrimony benefited from an efficient protection from the Brazilian substantive law. Nevertheless, this condition has been profoundly changed by Decree n. 6.640/2008, which modified the structure of Decree n. 99.556/1990, our most effective cave protection rule. This change had the purpose of introducing a new legal framework, that jeopardizes the integrity of most part of caves located in national territory, and, for that reason, demands efficient interpretations in order to minimize the noxious impacts on the environment. Answering that call, this work aimed to analyze not only the Decree in case, but also, in a general way, the Brazilian substantive law available to protect the natural underground cavities. To achieve such goal, law doctrine, case law, as well as deductive, inductive and analogical reasoning has been used. Federal Constitution and Federal rules have been examined: either those rules designed especially to protect the speleological patrimony or those which are useful for cave protection despite not being issued for that very reason. Some of the main State cave protection rules, especially the ones based on States Constitutions, have also been seen. At the end, an expressive range of the national rules available to protect the speleological patrimony has been explored. Concerning specifically to the changes in the Decree n. 99.556/1990, it has been shown that they couldn t have been made by another decree, which consisted violation of the Brazilian Constitution. Regarding the substantive aspects of the changes, an interpretation track has been chosen in order to, as much as possible, minimize the environmental losses and keep compatibility with the Federal Constitution